AN APPRAISAL OF THE TAX EVASION AND TAX AVOIDANCE SYSTEM IN INDONESIA - Rahmawati Rahmawati; Saifullahi Shehu Ibrahim (Akuntabilitas, 2015)
Tax avoidance and evasion are pervasive in all countries. This paper, firstreview a literature that integrate the tax avoidance and evasion into overall decisionproblem faced by government. The second, reviews the issue of corruption andbureaucracy, there is a link between tax evasion and corruption. This study uses literatureto analyze the cause and the effect of tax evasion and tax avoidance to environment.Finally, this paper will examine the effect of perceived corruption in government on taxevasion and how should the tax system in Indonesia face the tax evasion problem. Thegovernment attempts to improve the tax compliance in Indonesia with comprehensiveregulation of the schemes of tax avoidance schemes. Therefore, it need a specific antiavoidancerules in Indonesian tax lawDOI: 10.15408/akt.v8i2.2880